Peran Aktivitas Fisik Dalam Pengelolaan Diabetes Melitus Tipe 2 - Jajang Ganjar Waluya; Eli Amaliyah; Syafrina Arbaani Djuria; Ike Puspasari Ayu (Jurnal Kesehatan Panca Bhakti Lampung, 2025)
Introduction: Physical activity is considered the cornerstone of non-pharmacological management programs for type 2 diabetes mellitus. Objective: This study is to assess the effect of physical activity on type 2 diabetes mellitus in adults. Method: the framework used is from Arksey and O'Malley, consisting of 1) formulating research questions, 2) identifying relevant studies, 3) selecting studies, 4) extracting data, and 5) compiling, summarizing, and presenting findings. This review is driven by two research questions, namely: 1) What types of physical activity and exercise are provided in the management of Type 2 DM. 2) What is the impact of physical activity on Type 2 DM. This literature review includes studies on physical activity and exercise as interventions for the management of Type 2 DM. Randomized Controlled Trial (RCT) study design. The keywords used in this review were â€œPhysical Activityâ€ OR â€œExerciseâ€ AND â€œType 2 Diabetes Mellitusâ€. A literature search was conducted from January 2025 to March 2025 in the electronic database PubMed. Results: Eight research articles were obtained for review. During any type of physical activity, glucose uptake into active skeletal muscle increases via insulin-independent pathways. Conclusion: Physical activity, whether aerobic, resistance training and combined physical exercise following guidelines, can significantly reduce hyperglycemia and control glucose homeostasis in Type 2 DM patients. Recommendation: It is important to maintain a healthy body composition for type 2 diabetes patients. Aerobic and resistance exercise are recommended to control glucose homeostasis.